135k views
4 votes
Please tell me how I’m not getting it

Please tell me how I’m not getting it-example-1

1 Answer

2 votes


\bf f(x) = x^2-2 \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ \boxed{a}\\[2em] [f(a)]+1\implies [x^2-2]+1\implies x^2-1 \\\\[-0.35em] ~\dotfill\\\\ \boxed{b} \\\\ f(a+1)\implies \stackrel{x = a+1}{(a+1)^2-2}\implies \stackrel{FOIL}{a^2+2a+1}~~-2\implies a^2+2a-1 \\\\[-0.35em] ~\dotfill\\\\ \boxed{c}\\\\ f(c+b)\implies \stackrel{x = c+b}{(c+b)^2-2}\implies \stackrel{FOIL}{c^2+2cb+b^2}~~-2\implies c^2+2cb+b^2-2

User Tudor
by
5.4k points